From Traditional to Exceptional: Impact of the Use of Dried Chicken Meat Powder on Sensory and Nutritional Quality of Tarhana - Ramazan Ulku Cetin; Zeynep Kilci; Kivilcim Ates; Dogan Kaya; Arzu Akpinar-Bayizit (Fermentation)
Tarhana is a popular Turkish fermented food, made of a mixture of cereal and yoghurt, generally consumed as soup. Both lactic acid bacteria and yeasts are responsible for the fermentation. The selection and proportions of ingredients integrated along with the production process specify the nutritional value and sensory properties of the final product. Therefore, the first objective of the present study was to process a dried “chicken meat powder (CMP)” that could be used in food formulations. The second objective was to determine the impact of CMP addition on the nutritional and sensorial properties of Uşak tarhana recipe with geographical indication. In order to fulfill these challenges dried chicken meat powder (CMP) at levels of 20, 25, 30, and 35% were included in tarhana recipes for the very first time. Within the scope of the study, organoleptic properties of tarhana soups (control and CMP added) were determined, and the formulation with 30% CMP (TCMP30) achieved the highest sensory evaluation scores. This sample was analyzed further, and its physicochemical properties were compared to a control sample strictly following the traditional Uşak tarhana recipe. In the tarhana samples, the moisture, protein, and total fat content increased with higher CMP additions, while the ash, crude cellulose, carbohydrates, energy, salt, and dietary fiber decreased significantly (p < 0.05). The calcium and sodium contents decreased, however, potassium, phosphorus, and zinc contents increased. The fatty acid composition analysis revealed that Uşak tarhana contained more saturated fatty acids than either CMP or TCMP30; adding 30% CMP reduced the total saturated fatty acids while increasing the monounsaturated fatty acids. The main fatty acids in traditional samples were linoleic, palmitic, and oleic acids, comprising 83.82% of the total fat. In TCMP30, the order changed to oleic > linoleic > palmitic with 83.89% of total fat. Over time, the total phenolic content and antioxidant capacity decreased in the control sample but increased in TCMP30. These results suggest that a formulation including 30% CMP effectively enhances the sensory, functional, and nutritional aspects in tarhana.